Scientific Imaging with Digital Cameras. (July 2000) - Spring, Kenneth R.
The new BioImaging column of BioTechniques will feature short articles devoted to microscopy and digital imaging. The subject matter will address details of the methods used to produce images of cells and tissues at any magnification and resolution, and might include "tricks-of-the-trade", novel methods of specimen preparation, practices of image collection, tips on the digital manipulation and publication of images and historical perspectives.